Tentações de um “Historiador falhado”: o cerco da história na operação ficcional de José Saramago - Braúna, José Dércio (2022)
Having called himself a “failed historian”, with the flaw being heard in the sense of not having been able to obtain an academic training in this area of history, the Portuguese writer José Saramago (1922-2010), Nobel Prize in Literature in 1998, did not let, however, think and die sober the story. Through the books he conceived, provocations about the historiographical work are spread. Starting from the analysis of his novel História do Cerco de Lisboa (1989), but not restricting itself to it, this investigation aimed to understand the ways in which this writer made use of a whole instrument of historiographical practice - what Michel de Certeau called the “historiographical operation” – in its fictional operation. Being a writer who, several times, considered himself a seist with characters more than José Saramago himself, a novel (colloquiums, interviews, articles) reiterated in his interventions, both in the writing of his novels, his debt to historians in relation to a yours is to understand temporality and the ways in which this understanding is configured in the history that is written and taught. In História do Cerco de Lisboa there is precisely a questioning, of the adulteration of a historical text by a reviewer, of the problems of an “Accredited History” that only what has already been said; the history that, in doing so, therefore, does not carry out the necessary work of revisiting the documentary sources and the historiographical texts that have focused on them; the history that does not pay attention to its irrevocable revising character, because if all history is written from a given present, the questions that it poses to the vestiges of the past have their historicity. Starting from this novel with the name of history – História do cerco de Lisboa –, this investigation in question of continuing José Saramago's debate on these questions that were, as well as related to questions of persistence of historiography, such as the status of the fictional text can have in the historiographical work, in the sense of not being a mere source of research (document) but also an element that poses problems (theory).